Activation of amorphous bismuth oxide via plasmonic Bi metal for efficient visible-light photocatalysis - Li, Xinwei; Sun, Yanjuan; Xiong, Ting; Jiang, Guangming; Zhang, Yuxin; Wu, Zhongbiao; Dong, Fan (Journal of catalysis, 2017)
[Display omitted] •Bi-metal-decorated amorphous bismuth oxide photocatalysts were fabricated.•The Bi metal could activate the amorphous bismuth oxide via the SPR effect.•The photocatalytic performance can be well tuned via content of Bi metal.•Bi metal/amorphous bismuth oxide displayed enhanced photocatalytic activity.•The photocatalysis mechanism was revealed with ESR and in situ DRIFT. Amorphous semiconductors are seldom exploited as effective photocatalysts, as they are restricted by abundant bulk defects as carrier recombination centers. To activate amorphous bismuth oxide for efficient visible-light photocatalytic performance, a novel and facile strategy was developed. Plasmonic Bimetal-decorated amorphous bismuth oxide (Bi–BiO) was prepared by partial reduction with NaBH4. The content of Bi metal and the photocatalytic activity of the catalysts can be modulated by controlling the concentration of NaBH4 solution. Various techniques were employed to explore the structural features, optical properties, and active species during photocatalysis. The as-synthesized Bi–BiO catalysts were applied in photocatalytic removal of NO in air under and exhibited highly enhanced visible light photocatalytic activity. The significantly increased photocatalytic capability can be attributed to the combined effects of the enhanced visible light absorption and the improved separation efficiency of the charge carriers attributed to the surface plasmon resonance conferred by Bi metal. The advanced Bi–BiO catalysts also exhibited high photochemical and structural stability under repeated irradiation. Moreover, in situ DRIFT was carried out to reveal the time-dependent evolution of reaction intermediates during photocatalytic NO oxidation. A molecular-level photocatalysis mechanism was first proposed for Bi–BiO based on ESR and in situ DRIFT. This work could provide a new perspective in utilizing non-noble-metal Bi as a key activation factor to trigger the photocatalytic ability of amorphous semiconductors.